Distributed denial of service attacks : concepts, mathematical and cryptographic solutions - Ram, Mangey; Singh, Rajeev; Singh, Rajeev (De Gruyter Series on the Applications of Mathematics in Engineering and Information Sciences ;, 2021)
This book presents new concepts against Distributed Denial of Service (DDoS) attacks. It follows a systematic approach providing cryptographic and mathematical solutions that include aspects of encryption, decryption, hashing techniques, digital signatures, authentication, probability, statistical improvements to machine learning and soft computing as well as latest trends like blockchains to mitigate DDoS attacks.